Pharmacological modulation of apoptosis signaling in neurons of ca1-zone of hippocampus of rats with chronic alcohol intoxication - Belenichev, I. F.; Sokolik, Elena; Abramov, Andrej; Бєленічев, Ігор Федорович; Соколик, Олена Петрівна; Абрамов, Андрій Володимирович (India: Innovative Journal, 2011)
Patients with chronic alcohol intoxication have diffuse changes extended on all nervous system and local defeat (parenchymal disintegration, gliosis hems, haemorrhage). Research on new ways of pharmacocorrection of morphofunctional changes in neuro-glial structures of the brain and restoration of interneural interactions at modelling of 30-day chronic alcoholic intoxication in rats, has defined effective neuropeptide cerebroprotectors (cerebrolisin, cоrtexin and cerebrocurin). Also, results of experiment have shown that the most active preparation is cerebrocurin, so it is recommended for inclusion in the traditional scheme in treatment of chronic alcoholic intoxication.
Keywords: neuron; Вс1-2; apoptosis; alcoholism; cerebrocurin; neuroprotection